2022
DOI: 10.3389/fphys.2022.951979
|View full text |Cite
|
Sign up to set email alerts
|

Mitosis, Focus on Calcium

Abstract: The transformation of a single fertilised egg into an adult human consisting of tens of trillions of highly diverse cell types is a marvel of biology. The expansion is largely achieved by cell duplication through the process of mitosis. Mitosis is essential for normal growth, development, and tissue repair and is one of the most tightly regulated biological processes studied. This regulation is designed to ensure accurate segregation of chromosomes into each new daughter cell since errors in this process can l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 95 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…The enhanced Ca 2+ transfer into the mitochondria in mitosis may affect the spatial dynamics of Ca 2+ signals, which have been historically implicated in mitosis progression. 38 , 39 , 40 For example, localized Ca 2+ transients have been associated with the metaphase-to-anaphase transition, 41 , 42 and have been detected at the centrosomes in mitosis. 43 Ca 2+ signals have also been shown to be dispensable for entry into meiosis but required for the transition of the anaphase.…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced Ca 2+ transfer into the mitochondria in mitosis may affect the spatial dynamics of Ca 2+ signals, which have been historically implicated in mitosis progression. 38 , 39 , 40 For example, localized Ca 2+ transients have been associated with the metaphase-to-anaphase transition, 41 , 42 and have been detected at the centrosomes in mitosis. 43 Ca 2+ signals have also been shown to be dispensable for entry into meiosis but required for the transition of the anaphase.…”
Section: Resultsmentioning
confidence: 99%
“…Jun et al (2019) also demonstrated that loading MTA with cerium nanoparticles promoted a significant increase (90%) in the viability of human dental pulp stem cells (hDPSCs), leading to odontoblastic differentiation [24]. It is well known that calcium ions are important in cellular division processes [54,55]. They play a fundamental role in activating or inhibiting many intracellular reactions that control cell cycles, especially mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed another study looking at neurons, another postmitotic cell, failed to see protection from cadmium-induced cell death when inhibiting the mitochondrial calcium uniporter (Tang et al, 2021). Calcium signaling in general and specifically calmodulin, calcium release via the IP3 receptor, and activation of the mitochondrial uniporter have all been shown to be important for the progression of mitosis (Lagos-Cabré et al, 2020; Nugues et al, 2022; Rasmussen and Means, 1989; Takuwa et al, 1995; Zhao et al, 2019). Therefore, mitotic cells may be more sensitive to cadmium-induced alterations in these calcium signaling pathways.…”
Section: Discussionmentioning
confidence: 99%